Haplotype variation of estrogen receptor-alpha (ER-alpha) gene exon 4 in Turkish sheep breeds. - Ozmen, O.; Seker, I.; Kul, B.C.; Ertugrul, O. (My University, 2012)
Estrogen receptor a (ERalpha) gene has previously been found to related with sexual development and reproduction. In this study, on the basis of the sequences of human, cattle and caprine estrogen receptor a (ERalpha) genes, available in the GenBank database, sets of PCR primers were designed and used to amplify the ovine ERalpha gene exon 4 region. We identified six single nucleotide polymorphisms (SNP) in the ERalpha exon 4. Some variations determined for exon 4 g.43A > G, p.T43A; g.49C > T, p.L49F; g.178A > T, p.T178S led to changes in the amino acids, but no amino acid changes were determined in g. 18G > C, g.27C > T, g.96G > A. These fragments were deposited in the GenBank database under accession number: JF262030-JF262035. It was noted in particular that White Karaman and Awassi breeds were similar to each other, whereas the Chios breed had a different variation.
Keywords: Animals; Breeding; Estrogen Receptor alpha; Exons; Haplotypes; Mutation; Sheep, Domestic; Turkey; estrogen receptor alpha; animal; article; breeding; exon; genetics; haplotype; mutation; sheep; Turkey (republic)